The legal rules of Publishing Crime-related Articles in the Media: a Comparative Study - grimes, sara; lebdjiri, noueddine (The journal of Teacher Researcher of Legal and political Studies, 2025)
This study sought to monitor a number of the most important rules regulating the publishing of crime in Algerian legislation, whether the rules provided by the Algerian process of publishing crime news in the media in the light of Algerian legislation, whether stipulated in the penal code or in the media law, and comparing it with some Arab legislation. The study also sought to present a set of rules stipulated by some Arab legislation, which the researchers did not find a mention in the Algerian legislation. The importance of the study emerges from its connection to the topic of crime on the one hand, and to the process of publishing and broadcasting through the media, with its influential power that doubles the danger of publishing such topics (Times New Roman, Size 14, Interline 1cm).